Reflections on people, policy, and practices in curriculum history - Morowski, Deborah L.; Burlbaw, Lynn M. (Research in curriculum and instruction., 2024)
"America's schools are constantly in the news today for safety concerns, contested curricula, teacher quality, test scores, and a variety of other topics. Although most people spend at least 12 years in school systems, they know little of the history or evolution of American schooling. The collection of papers assembled in this book are divided into three categories which greatly impacted American schooling: people, policy, and practices. This work seeks to shed light on what has occurred in curriculum history in the past so as to help readers develop a deeper understanding of how our system of schooling arrived at its current state. The first section of the book examines the stories of people who had an influence on schooling and education. The second section focuses on the curricula and programs that were utilized in schools and districts throughout the country. The final chapter of the book looks at decisions that had long-ranging impact on educational policies. The chapters of this book offer a glimpse into the history of American schooling and those people, policies, and practices that influenced its development. It is the editors' hope that the work will spark interest in scholars and students of educational history to examine other past, as well as present, stories of educators to expand our understanding of the saga that is the American schooling experience"--